The embryonic Brachyury transcription factor is a novel biomarker of GIST aggressiveness and poor survival - Pinto, Filipe Manuel Teixeira (2016)
The T-box transcription factor Brachyury was recently reported to be upregulated and associated with prognosis in solid tumors. Here, we proposed to evaluate the potential use of Brachyury protein expression as a new prognostic biomarker in gastrointestinal stromal tumors (GIST). Brachyury protein expression was analyzed by immunohistochemistry in a cohort of 63 bona fide GIST patients. Brachyury expression profiles were correlated with patients' clinicopathological features and prognostic impact. Additionally, an in silico analysis was performed using the Oncomine database to assess Brachyury alterations at DNA and mRNA levels in GISTs. We found that Brachyury was overexpressed in the majority (81.0 %) of primary GISTs. We observed Brachyury staining in the nucleus alone in 4.8 % of cases, 23.8 % depicted only cytoplasm staining, and 52.4 % of cases exhibited both nucleus and cytoplasm immunostaining. The presence of Brachyury was associated with aggressive GIST clinicopathological features. Particularly, Brachyury nuclear (with or without cytoplasm) staining was associated with the presence of metastasis, while cytoplasm sublocalization alone was correlated with poor patient survival. Herein, we demonstrate that Brachyury is overexpressed in GISTs and is associated with worse outcome, constituting a novel prognostic biomarker and a putative target for GIST treatment.